A Dopamine Sensor Based on Pre-Concentration by Magnetic Nanoparticles - Mojtaba Bagherzadeh; Somayeh Ansari; Fariborz Riahi; Anahita Farahbakhsh (International Journal of Electrochemistry)
Herein, Fe3O4 magnetic nanoparticles (MNPs) were synthesized and characterized. Afterward, a magnetic carbon paste electrode (MCPE) was modified with MNPs via casting and drying MNPs on top of the MCPE (MCPE/MNP). Electrochemical behavior of the MCPE/MNP was studied by cyclic voltammetry in the presence of [Fe(CN)6]3−/4− as a redox probe, and surface pKa of MNPs was evaluated as 6.3±0.1. The behavior of MCPE/MNP towards dopamine (DA) and ascorbic acid (AA) has been investigated by electrochemical methods, and the obtained results showed that the MCPE/MNP has adsorption behavior towards only DA. Based on this behavior, the DA molecules were pre-concentrated on top of the MCPE/MNP and followed with stripping in DA free solution. Subsequent to experimental and instrumental optimization, a calibration curve from 5.0×10-6 to 1.0×10-3 M DA with r2=0.999, DL = 7.6×10-7 M DA, and RSD = 4.6%, was obtained in the presence of 1.0×10-3 M AA. Performance of the MCPE/MNP was successfully tested in a pharmaceutical sample.